Linguistic Interfaces in East-Asian Languages A Festschrift in Honor of Yoshihisa Kitagawa - Ting, Jen; Hsu, Yu-Yin (Studies in East Asian Linguistics, 2024)
XXV, 259 p. 264 illus., 5 illus. in color.